Virtual Planning and Allograft Preparation Guided by Navigation for Reconstructive Oncologic Surgery: A Technical Report - Ritacco, Lucas E. (JBJS Essent Surg Tech, 2017)
INTRODUCTION: Advanced virtual simulators can be used to accurately detect the best allograft according to size and shape. INDICATIONS & CONTRAINDICATIONS: STEP 1: ACQUISITION OF MEDICAL IMAGES: Obtain a multislice CT scan and a magnetic resonance imaging (MRI) scan preoperatively for each patient; however, if the time between the scans and the surgery is >1 month, consider repeating the MRI because the size of the tumor may have changed during that time. STEP 2: SELECT AN ALLOGRAFT USING VIRTUAL IMAGING TO OPTIMIZE SIZE MATCHING: Load DICOM images into a virtual simulation station (Windows 7 Service Pack 1, 64 bit, Intel Core i5/i7 or equivalent) and use mediCAS planning software (medicas3d.com) or equivalent (Materialise Mimics or Amira software [FEI]) for image segmentation and virtual simulation with STL (stereolithography) files. STEP 3: PLAN AND OUTLINE THE TUMOR MARGINS ON THE PREOPERATIVE IMAGING: Determine and outline the tumor margin on manually fused CT and MRI studies using the registration tool of the mediCAS planning software or equivalent (Materialise Mimics software.) STEP 4: PLAN AND OUTLINE THE SAME OSTEOTOMIES ON THE ALLOGRAFT: Determine and outline the osteotomies between host and donor using the registration tool of the mediCAS planning software or equivalent (Materialise Mimics software.) STEP 5: ASSESS THE PATIENT AND ALLOGRAFT IN A VIRTUAL SCENARIO: Be sure to consider the disintegration of bone tissue that occurs during the osteotomy and corresponds to the thickness of the blade (approximately 1.5 mm). STEP 6: NAVIGATION SETTINGS: A tool of the mediCAS planning software allows the virtual preoperative planning (STL files) to be transferred to the surgical navigation format, DICOM files. STEP 7: PATIENT AND ALLOGRAFT INTRAOPERATIVE NAVIGATION: The tumor and allograft are resected using the navigated guidelines, which were previously planned with the virtual platform. RESULTS: The 3D virtual preoperative planning and surgical navigation software are tools designed to increase the accuracy of bone tumor resection and allograft reconstruction(3). PITFALLS & CHALLENGES: